(untitled) (London Journal of Medical and Health Research, 2023)
Background: More than 85% of women in union are not using modern contraceptives in 2006 and 2017 respectively. The contraceptive prevalence rate remains low and unmet need is still high. The massive adherence of the population to family planning remains a major concern in the Republic of Benin. Objective: The aim of this study is to analyse the overall trend in factors of non-use of modern contraceptive methods among married or cohabiting women from 2006 to 2017. Data and methods: The data analysed come from the Benin Demographic and Health Surveys (EDSB) conducted in 2006 and 2017-2018. The description of contraceptive variation was done using bivariate descriptive methods, the identification of resistance factors to contraceptive use from a binary logistic regression model and the analysis of observed changes in contraceptive practice from 2006 to 2017 by the Oaxaca-Blinder multivariate decomposition method. Results: Fear of side effects and opposition from women or partners were the main reasons given by women in union in 2006 (21.0%; 11.4%) and 2017-2018 (18.4%; 35.5%) for refusing to use modern contraceptives. At the bivariate level, except for the variables information received on family planning in 2017 and number of child deaths, a significant association at the 1% level was established between non-use of modern methods and the independent variables. However, a decrease in proportion was recorded in the different subgroups of variables and especially in contraceptive decision-making. With a difference of 51 points, 70.8% of women reported not making a decision to use contraceptives within the couple in 2006 versus 19.5% in 2017. The Oaxaca-Blinder multivariate decomposition revealed that 87.5% of the observed changes in contraceptive use were due to differences in coefficients and 12.4% to differences in characteristics. Family planning information, religion, department of residence, household standard of living, number of deceased children, contraceptive decision, and husband’s desire to have children were significantly associated with non-use of modern contraceptives between 2006 and 2017. Recommendations: Family planning programmes and policies should be strengthened in all departments by involving spouses and partners more. Lifestyle improvement measures should be encouraged to ensure equitable access to contraceptives.